1999
DOI: 10.1007/s004280050444
|View full text |Cite
|
Sign up to set email alerts
|

Innervation of human adrenal gland and adrenal cortical lesions

Abstract: The innervation of the human adrenal gland and of cortical lesions was studied in sections of cortical tissue (n=10), hyperplastic cortical tissue (n=3), and tissue from cortical adenomas (n=5) and carcinomas (n=6). The presence and distribution of nerve structures containing neuronal markers indicating sympathetic and parasympathetic innervation were studied by immunohistochemistry and the co-existence and co-localization patterns of the different markers by immunofluorescence. The cortex and hyperplastic cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…Staining was carried out with 3,3Ј-diaminobenzidine, and counterstaining was carried out with hemalum. Adrenal gland tissue served as a positive internal and external control (24,25).…”
Section: Methodsmentioning
confidence: 99%
“…Staining was carried out with 3,3Ј-diaminobenzidine, and counterstaining was carried out with hemalum. Adrenal gland tissue served as a positive internal and external control (24,25).…”
Section: Methodsmentioning
confidence: 99%
“…The role of SV2 in breast cells could be associated to secretory nature of mammary glands, and may interact with other vesicle proteins such as synaptobrevin, which is essential for secretion but not for the development of synaptic process (Ahnert-Hilger et al, 1996), however, the SV2 role in cancer is not clear, although it is already reported in others types of cancer, for instance, brain (de Groot et al, 2010;, pancreas (Jakobsen et al, 2002), gastrointestinal tract (Jakobsen et al, 2002;Bumming et al, 2007 ), liver (Hanoun et al, 2010), bladder (Coelho et al, 2010), prostate (Karsenty et al, 2009) and adrenals (Li et al, 1999) tumors among others, where SV2 has already been proposed as molecular and transdifferentiation marker of neural nature (Nilsson et al, 2004;Zhang et al, 2010). This is possible because in the cancerous state the terminal differentiation to the anticipated cellular type is altered and the phenomena of lineage infidelity that is associated with the ability of cancer cells to transdifferentiate, occurs in different cancer types and occur in breast cancer (Zhang et al, 2010); thus, it is a commune phenomenon that cancer cell turns-off/-on non-habitual genes changing the ontogeny to evade the immune system and hold the linage independence.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of secretory vesicles is characteristic in synaptic (de Groot et al, 2010;, gastric (Bumming et al, 2007), pancreatic (Jakobsen et al, 2002), adrenal (Li et al, 1999) and prostatic (Karsenty et al, 2009) cells which synaptic vesicular receptor (SV) play an important role in exocytosis and secretory process of synaptic (de Groot et al, 2010) and endocrine cells, (Dong et al, 2006;Coelho et al, 2010), but when cancer occurs this protein tends to overexpress in brain (de Groot et al, 2010), neuroendocrine (Portela-Gomes et al, 2000), gastrointestinal (Bumming et al, 2007) and prostate (Karsenty et al, 2009) is not clear neither it has been reported in breast cells, but its role as molecular marker of cancer in others organs and tissues has been increasing in recent years (Portela-Gomes et al, 2000;Zhang et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…32 In general, nerve fibers have been rarely observed in human tumors. [33][34][35] Interestingly, in adrenal cortical tumors, also known to express NPY receptors, 10 nerve fibers have been identified that were also shown to contain NPY. 35 These reports, together with the present results, demonstrate that NPY-positive nerve fibers can grow into certain human tumors.…”
Section: Discussionmentioning
confidence: 99%
“…[33][34][35] Interestingly, in adrenal cortical tumors, also known to express NPY receptors, 10 nerve fibers have been identified that were also shown to contain NPY. 35 These reports, together with the present results, demonstrate that NPY-positive nerve fibers can grow into certain human tumors. Furthermore, the present observations may also suggest that NPY released from perivascular and interstitial intratumoral nerve fibers could bind to the NPY receptors of tumor vessels and tumor cells, respectively.…”
Section: Discussionmentioning
confidence: 99%